Identifying climatic risk to soybean cultivation in the transitional type of moderate climate in Central Poland - Jacek Żarski; Renata Kuśmierek-Tomaszewska; Stanisław Dudek; Michał Kropkowski; Remigiusz Kledzik (Journal of Central European Agriculture, 2019)
Meteorological measurements carried out in 1986-2015 were used to evaluate the climatic risk for soybean cultivation in the transitional type of moderate climate in Poland, as well the directions and the significance of changes in the meteorological indices were considered. Their analysis led to determination of the following unfavourable climatic conditions for soybean cultivation: shortening of the active growth period, a delay of the date on which the soil warms up to 8 °C at a depth of 5 cm, occurrences of meteorological and agricultural droughts and of late spring ground frosts. All indices of the climatic risk in soybean cultivation demonstrated high temporal variability. Significant trends of changes for the following indices were observed: an increase in the number of moderate and strong frosts and an earlier start of the period when soil reaches 8 °C at a depth of 5 cm. For 2000-2015, in relation to the previous 15-year period of 1986-2000, it was found that temporal variability increased for the number of moderate and strong late spring frosts and for the date of the last late spring frost. On the other hand, variability was reduced as regards the beginning and the length of the period of active growth of plants, as well as precipitation shortages and surpluses in the period when soybean water needs are intensified.